Association between Pseudonocardia symbionts and Atta leaf-cutting ants suggested by improved isolation methods - Marsh, Sarah E.; Poulsen, Michael; Gorosito, Norma B.; Pinto-Tomás, Adrián; Masiulionis, Virginia E. [UNESP]; Currie, Cameron R. (My University, 2013)
Fungus-growing ants associate with multiple symbiotic microbes, including Actinobacteria for production of antibiotics. The best studied of these bacteria are within the genus Pseudonocardia, which in most fungus-growing ants are conspicuously visible on the external cuticle of workers. However, given that fungus-growing ants in the genus Atta do not carry visible Actinobacteria on their cuticle, it is unclear if this genus engages in the symbiosis with Pseudonocardia. Here we explore whether improving culturing techniques can allow for successful isolation of Pseudonocardia from Atta cephalotes leaf-cutting ants. We obtained Pseudonocardia from 9 of 11 isolation method/colony component combinations from all 5 colonies intensively sampled. The most efficient technique was bead-beating workers in phosphate buffer solution, then plating the suspension on carboxymethylcellulose medium. Placing these strains in a fungus-growing ant-associated Pseudonocardia phylogeny revealed that while some strains grouped with clades of Pseudonocardia associated with other genera of fungus-growing ants, a large portion of the isolates fell into two novel phylogenetic clades previously not identified from this ant-microbe symbiosis. Our findings suggest that Pseudonocardia may be associated with Atta fungus-growing ants, potentially internalized, and that localizing the symbiont and exploring its role is necessary to shed further light on the association.
Keywords: Actinobacteria; Atta leaf-cutter ants; Mutualism; Pseudonocardia; Symbiosis